2022
DOI: 10.21705/mcbs.v6i2.232
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP2A6 Genetic Polymorphism and Lung Cancer in Female Never Smokers

Abstract: Background: The major significant factor that affected lung cancer development among female passive smokers is environmental tobacco smoke. Nicotine can be found in a never smoker population, such as a child whose father is a smoker. Lung carcinogenesis in never smoker populations is affected by nicotine metabolism by CYP2A6 gene, which encodes the main nicotine metabolizing-enzyme. The aim of this study was to assess the genetic polymorphism of CYP2A6 and its association with secondhand smokers among females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…14,21 Increased ROS can cause oxidative stress, which leads to DNA damage and apoptotic processes that cause a decrease in the number of Leydig cells and ultimately in testosterone levels. 22,23 Therefore, the administration of antioxidants is considered a potential strategy for treating male infertility. 24,25 This study showed that administration of green tea kombucha, specifically at 1 ml/day for 28 days, was shown to increase Leydig cell numbers and testosterone levels in male Wistar rats exposed to electric cigarette vapor.…”
Section: Discussionmentioning
confidence: 99%
“…14,21 Increased ROS can cause oxidative stress, which leads to DNA damage and apoptotic processes that cause a decrease in the number of Leydig cells and ultimately in testosterone levels. 22,23 Therefore, the administration of antioxidants is considered a potential strategy for treating male infertility. 24,25 This study showed that administration of green tea kombucha, specifically at 1 ml/day for 28 days, was shown to increase Leydig cell numbers and testosterone levels in male Wistar rats exposed to electric cigarette vapor.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of several human diseases is often associated with specific genetic variants. [18][19][20] Genetic variants related to folate metabolism and their association with congenital heart defects have been studied extensively. 21 Vitamin B12 plays an important role in folate and homocysteine metabolism.…”
Section: Discussionmentioning
confidence: 99%